'n Eksegetiese ondersoek na die teologiese inhoud van Sefanja 1:7-13 - SD Snyman (Acta Theologica)
The question posed in this contribution is the question of theological intent. What kind of theology is portrayed in Zephenaiah 1:7-13? To answer this question an exegesis of this pericope is offered focusing on the text-internal (demarcation of the text, text critical problems and structure) and text-external (Gattung, Sitz im Leben, tradition material, redactional issues) features of the text. The conclusion reached is that this percope wants to highlight religious indifference on the part of the people of God.